Self-monitoring – usability evaluation of heart rate monitoring using wearable devices in patients with acquired brain injury. (1st November 2020) - Støve, Morten P.; Larsen, Birgit T.
Abstract: Aim: It is recommended that patients with acquired brain injury learn to self-monitor their exertion and track physical activity, but current technology may offer limited usability. Wearable devices demonstrate good potential to overcome the limitations of the current technology, however, the usability for patients with acquired brain injuries are currently unknown. Methods: In this study, the usability and applicability of a wearable device were analysed based on qualitative subjective participant and therapeutic ratings and a semi-structured focus-group interview. Twenty-five participants with acquired brain injuries from an inpatient rehabilitation clinic were enrolled and participants wore the Garmin Forerunner (GF) 235 during daily therapeutic rehabilitation activities for 3 weeks. Conclusions: This study provided unequivocal results indicating limited usability of the GF 235 for patients with severe motor and cognitive impairments following acquired brain injury. Several important factors were identified that limited usability and important key demands and requirements for devices to be used for patients with acquired brain injury were suggested. We conclude that motor and cognitive function partly affects usability and applicability of wearable devices and the study provided imperative insight into the importance of motor and cognitive status when using wearable devices for patients with acquired brain injury.